The power of emotional experience. Sociological reflections on emotions as instruments for bio-psycho-social well-being - D'Ambrosio, Mariangela (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The power of emotional experience is central to many transdisciplinary studies, highlighting emotions as complex relational processes with “rationality” and as tools for holistic well-being. This essay examines emotion-based behaviours through classical and emotion sociology within the context of human flourishing. It also shares outcomes from two social research studies: one focusing on college students in the post-pandemic period and the other on professional supervision of social workers.